TINDAKAN PENGAWASAN PEMERINTAH DAERAH PADA PENCEGAHAN PEMBAKARAN HUTAN DALAM RANGKA PERLINDUNGAN LINGKUNGAN DI PROVINSI RIAU: Local Government Supervisory Actions On Prevention Of Forest Burning In The Framework Of Environmental Protection In Riau Province - Sabrina Rahmadini Utomo; Narita Adityaningrum (Faculty of Law, Universitas Trisakti, 2025)
Preventive local government supervision actions, one of which is to prevent the problem of burning land / forests as a result of people who do not understand the negative impacts on the environment. Local governments should ensure that supervision runs according to their authority based on the principle of regional autonomy and the principle of environmental protection. Formulation of the problem in this article is about the supervision carried out by local government in preventing forest fires in Riau Province whether it is in accordance with Regional Regulation Number 1 of 2019. The results and conclusion are supervision carried out by Riau Provincial Government in preventing forest fires in its territory, including Kuantan Singingi Regency. In terms of supervisory action in form of prevention, Regional Government often does not provide warnings in each region to perpetrators who clear land by burning. This violates regional authority to protect environment in accordance with principle of decentralization (delegation of authority from central government to regional government). Local governments are obliged to carry out preventive action by increasing supervision, including by dividing the area, making it easier to reach if a fire occurs, regulating conditions over season, especially during strong winds, and maximizing monitory.